2022
DOI: 10.1159/000526863
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic Burden, Polypharmacy, and Cognition in Parkinson’s Disease Patients with Mild Cognitive Impairment: A Cross-Sectional Observational Study

Abstract: <b><i>Introduction:</i></b> Anticholinergic burden may be an important risk factor for the cognitive impairment. Especially in polypharmacy, even drugs with low anticholinergic effects may contribute to a significant anticholinergic burden. The drugs with anticholinergic effects are used in treatment of motor and nonmotor symptoms of Parkinson’s disease (PD). Therefore, it is important to screen for polypharmacy and anticholinergic burden in PD patients with mild cognitive impairment (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…In two studies using ACB, 15.5-18.5% of patients had more than 2 points and 41.5-46.3% took at least one anticholinergic drug; these seem to be similar results to those in our study [42][43][44]. Geriatric patients from the same area of Poland hospitalised in a geriatric ward had a lower anticholinergic burden (ACB ≥ 3 13.98%, ACB ≥ 1 40.73%) than PD patients from our study, which might suggest that the topic is especially relevant for PD patients [45].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In two studies using ACB, 15.5-18.5% of patients had more than 2 points and 41.5-46.3% took at least one anticholinergic drug; these seem to be similar results to those in our study [42][43][44]. Geriatric patients from the same area of Poland hospitalised in a geriatric ward had a lower anticholinergic burden (ACB ≥ 3 13.98%, ACB ≥ 1 40.73%) than PD patients from our study, which might suggest that the topic is especially relevant for PD patients [45].…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, some studies have not found any association between anticholinergics and cognitive decline in PD patients. However, their authors did suggest that this could be related to factors such as a low anticholinergic burden in the analysed group or a short follow-up [41][42][43].…”
Section: Discussionmentioning
confidence: 96%
“…In addition to the use of medicines with high ACB scores, high ACB may also result from the concomitant use of several low-risk medicines. 22 Hence, it is expected that there is a positive correlation between the number of medicines an individual takes and the resultant ACB. This is in agreement with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Anticholinergic burden has been linked to functional and cognitive decline in PwP, with possible contribution to overt dementia, and potential side effects including constipation, agitation, urinary retention, and delirium ( 203 , 204 ). The use of anticholinergic indexes, such as Anticholinergic Drug Scale (ADS) and the Drug Burden Index - Anticholinergic Component (DBI-ACh), are useful clinical tool for such assessments, with ADS being shown to correlate with serum anticholinergic activity ( 203 , 205 , 206 ).…”
Section: Dashboard Vital: Co-morbidities Co-medications and Dopamine ...mentioning
confidence: 99%